MENINGKATKAN KEJUJURAN AKADEMIK: EFEKTIVITAS CLASSROOM DEVELOPMENTAL BIBLIOTHERAPY DALAM PEMBELAJARAN - Khotimah, Siti Khorriyatul; Fadhli, Mohamad Ivan; Habibi, Yasin (Universitas Ahmad Dahlan, 2017)
Academic honesty is one of character education that must be teached to our students integratedly in learning process. Bibliotherapy, especially developmental bibliotherapy is one of technics to teach values integrated in curriculum. This research aims is to find out the efectiveness of classrooom developmental bibliotherapy in Bahasa Indonesia learning to improve student’s academic honesty. This research aim is to test the influence of Classroom Developmental Bibliotherapy to increase academic honesty 4th grade students. The type of this research is Quasi Experimental Reseacrh using Non Equivalent Control group Posttest Only Design. This research take 63 subjects on 4th MI (Islamic Ememntary School) students. This research take 2 groups, devided into experimental and control groups. The treatment, CDB in learning given to experimental group in 4 sessions. CDB is given integratedly in Bahasa Indonesia Learning with 4 steps: pre-reading, guided-reading, post-reading disscussion, and reinforcement/ problem solving. The measurement of academic honesty is using The Academic Honesty Schale, wich measure academic honesty in 3 aspecs; attitude, tendency and behavior. The test result through t-test is t=2,454 with significance p= 0,020, indicate that there is difference of cheating behavior on experiment group and control group. It means that there is influence of role plaing method in learning to cheathing behavior on undergraduate students. Abstrak Kejujuran akademik merupakan salah satu nilai dalam pendidikan karakter yang harus diajarkan kepada siswa yang terintegrasi dalam proses pembelajaran. Biblioterapi, terutama biblioterapi perkembangan merupakan salah satu teknik untuk mengajarkan nilai yang terintegrasi dalam kurikulum. Tujuan penelitian ini adalah untuk menguji Efektifitas Classroom Developmental Bibliotherapy (CDB) dalam Pembelajaran Bahasa Indonesia untuk meningkatkan kejujuran akademik pada siswa. Jenis penelitian ini adalah eksperiment kuasi dengan desain Non Equivalent Control Group Posttest Only Design. Subyek dalam penelitian ini sejumlah 63 siswa kelas IV MI (Madrasah Ibtidaiyah), yang dibagi dalam dua kelompok, kelompok eksperimen dan kontrol. Perlakuan CDB dalam pembelajaran diberikan pada kelompok eksperimen dalam empat sesi. CDB diberikan secara integratif dalam pembelajaran Bahasa Indonesia dengan empat tahapan, yaitu prabaca, membaca terbimbing, diskusi pasca baca dan penguatan/ pemecahan masalah. Pengukuran kejujuran akademik menggunakan Skala Kejujuran Akademik, yang mengukur kejujuran akademik dalam tiga aspek; sikap, kecenderungan dan perilaku untuk menghindari mencontek. Dari hasil uji-t diketahui bahwa terdapat perbedaan tingkat kejujuran akademik pada kelompok eksperimen dan kelompok kontrol. Hal ini berarti CDB dalam pembelajaran Bahasa Indonesia efektif untuk meningkatkan kejujuran akademik siswa.Key word: academic honesty, classroom developmental bibliotherapy